Driving Sustainable Waste Management Through CSR and Green Accounting - Florence Olivia Moroki; Pricilia Joice Pesak (AIBPM Publisher, 2026)
Despite the increasing volume of medical waste in Indonesia, there is still limited understanding of how organizational strategies influence environmental performance in the healthcare sector. This study examines the roles of green accounting (GA) and corporate social responsibility (CSR) in shaping sustainable waste management (SWM), while also exploring whether waste management awareness (WMA) acts as a mediating factor. A quantitative approach was applied in a general hospital in Manado, using data collected from 109 purposively selected employees. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that CSR has a significant positive effect on SWM (t = 6.454, p 0.001), whereas GA does not have a significant effect (t = 1.682, p = 0.093). In addition, the indirect effects of GA (t = 0.090, p = 0.928) and CSR (t = 0.671, p = 0.502) through WMA are not significant, indicating that WMA does not function as a mediator. These findings suggest that sustainable waste management in hospitals is influenced more by institutional strategies than by individual awareness. From a practical standpoint, hospitals should prioritize the integration of CSR initiatives and strengthen the strategic use of GA to improve waste management performance.